2008
DOI: 10.3390/ijms9112194
|View full text |Cite
|
Sign up to set email alerts
|

Detection of FLT3 Oncogene Mutations in Acute Myeloid Leukemia Using Conformation Sensitive Gel Electrophoresis

Abstract: FLT3 (fms-related tyrosine kinase 3) is a receptor tyrosine kinase class III that is expressed on by early hematopoietic progenitor cells and plays an important role in hematopoietic stem cell proliferation, differentiation and survival. FLT3 is also expressed on leukemia blasts in most cases of acute myeloid leukemia (AML). In order to determine the frequency of FLT3 oncogene mutations, we analyzed genomic DNA of adult de novo acute myeloid leukemia (AML). Polymerase chain reaction (PCR) and conformation-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
4
3
0
1
Order By: Relevance
“…Also, the only study which was conducted in Saudi Arabia for FLT3 mutations in AML patients showed frequency of 20.15% (26/129), close to our results [11]. The explanations of lower frequency of FLT3 mutations in our study from other several studies may be explained by differences in the sizes of examined groups or might be due to population genetics, environmental factors, selected patient population studies, or because of differences of age as the median age of patients in this study was 36 years in comparison to comparative studies or a combination of the all.…”
Section: Discussionsupporting
confidence: 90%
“…Also, the only study which was conducted in Saudi Arabia for FLT3 mutations in AML patients showed frequency of 20.15% (26/129), close to our results [11]. The explanations of lower frequency of FLT3 mutations in our study from other several studies may be explained by differences in the sizes of examined groups or might be due to population genetics, environmental factors, selected patient population studies, or because of differences of age as the median age of patients in this study was 36 years in comparison to comparative studies or a combination of the all.…”
Section: Discussionsupporting
confidence: 90%
“…In patients with FLT3 and NPM1 mutations, the associations of other genetic alterations have also been evaluated to understand any possible role in disease outcome. The prevalence of FLT3 and NPM1 mutations found in this population was in coherence with other studies (Asian and Western) despite geographic and ethnic differences (Tables 3, 4) [19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 90%
“…[21][22][23] However, it was higher in South Korea (22.4%) and Australia (30.8%), while it was lower in Poland (8%) and Saudi Arabia (11.6%). [24][25][26][27] In line with many previously published studies, 28,30 it was reported that t (15,17) and chromosome 8 trisomy were the most significant recurrent alterations associated with FLT3-ITD mutation. Our data showed that most of all patients with FLT3-ITD mutation had t(15,17) followed by t(8:21).…”
Section: Discussionsupporting
confidence: 57%